2015
DOI: 10.18632/oncotarget.5736
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocation of EGFR regulates mitochondria dynamics and promotes metastasis in NSCLC

Abstract: Dysfunction of the mitochondria is well-known for being associated with cancer progression. In the present study, we analyzed the mitochondria proteomics of lung cancer cell lines with different invasion abilities and found that EGFR is highly expressed in the mitochondria of highly invasive non-small-cell lung cancer (NSCLC) cells. EGF induces the mitochondrial translocation of EGFR; further, it leads to mitochondrial fission and redistribution in the lamellipodia, upregulates cellular ATP production, and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 49 publications
0
79
0
Order By: Relevance
“…In recent years, a growing number of studies provided new insight into the role of mitochondria in cancer and demonstrated that impaired bioenergetic function of mitochondria is a hallmark of tumorigenesis [32,33]. It has been reported that mitochondrial alteration is correlated with cancer cell motility and invasiveness, as well as chemo-resistance [34][35][36]. We inferred that CDH18 might influence the function of mitochondria via UQCRC2, and thus inhibited the invasiveness and chemoresistance of glioma cells.…”
Section: Discussionmentioning
confidence: 82%
“…In recent years, a growing number of studies provided new insight into the role of mitochondria in cancer and demonstrated that impaired bioenergetic function of mitochondria is a hallmark of tumorigenesis [32,33]. It has been reported that mitochondrial alteration is correlated with cancer cell motility and invasiveness, as well as chemo-resistance [34][35][36]. We inferred that CDH18 might influence the function of mitochondria via UQCRC2, and thus inhibited the invasiveness and chemoresistance of glioma cells.…”
Section: Discussionmentioning
confidence: 82%
“…In this case, mitochondria need to fragment, in a Drp1-dependent way, in order to be transported and accumulate at the cell leading-edge, where they promote local ATP production, essential for lamellipodia formation, cell migration and metastasis formation [71]. The same was shown in non-small cell lung cancer (NSLCC) [72], in epithelial cancer cells [73] and malignant oncocytic thyroid tumors [70]. Interestingly, also TME-derived hypoxia is able to regulate both glioblastoma and breast cancer cell migration by promoting Drp1 transcription and stimulating mitochondrial fission [74,75].…”
Section: Mitochondrial Dynamics and Cell Migrationmentioning
confidence: 95%
“…EGFR (epidermal growth factor receptor) is an example for a receptor tyrosine kinase that has been shown to be translocated to mitochondria [22]. This finding differs from the previously discussed cases insofar as the ligand is not a low-molecular weight molecule such as steroids, T3 and the vitamin D 3 hormone, but represents a peptide of 53 amino acids.…”
Section: Egfr a Receptor Tyrosine Kinase In Mitochondriamentioning
confidence: 91%
“…Mitochondrial EGFR has been studied in detail in non-small-cell lung cancer cells. It was shown to be internalized by endocytosis and, thereafter, attached to mitochondria [22]. The translocation was stimulated by EGF.…”
Section: Egfr a Receptor Tyrosine Kinase In Mitochondriamentioning
confidence: 98%
See 1 more Smart Citation